Characteristics of operational control reliability of aircraft functional systems and avionics suites - S. V. Kuznetsov (Научный вестник МГТУ ГА, 2023)
The operational control system (OCS) of civil aircraft (A/C) airborne equipment is an important component of its technical operation system (TOS). Operational control is an integral part of the technical operation process. It makes it possible to assess the technical conditions (TC) of the objects to be monitored in various states of airborne equipment operation, aircraft preparation for flight, various types of maintenance and recovery. The main property of operational control is the reliability of control. The key task of operational control is not only to determine the type of technical condition, but also to quantify the correctness or erroneousness of decision-making. Control reliability characteristics (CRC) are quantitative indicators of the degree of objectivity in decision-making. Depending on the level of task details, it is necessary to distinguish the control reliability characteristics of units, functional systems (FS) and avionics suites for various means of operational control: built-in test equipment (BITE), on-board self-contained, ground-onboard and ground systems. The choice of the control reliability characteristics is based on the system analysis and the mathematical apparatus of logic, probability theory and mathematical statistics. Rational sets of technical states and decision-making about the technical conditions of functional systems and avionics suites are formed. Based on these sets, three groups of control reliability characteristics were identified. The first group consists of conditional probabilities of transitions in the operational control process under various types of control. The second group consists of unconditional probabilities of transitions in the operational control process under various types of control. The third group consists of a posteriori decision-making probability in the operational control process under various types of control. Analytical dependences for calculating the control reliability characteristics of three groups for functional systems and avionics suites and relationships between them are determined. The air-conditioning system was used to calculate the reliability of the control.